Protection of Traditional Culture and Customary Expressions from the Perspective of Customary Law - gia dina (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the protection mechanisms for traditional culture and customary expressions from a customary law perspective and to evaluate the extent to which these systems can be integrated into the national legal framework. The method used is qualitative legal research with a normative juridical and anthropological juridical approach. Data were collected through literature studies, interviews with customary leaders, and analysis of national and international legal documents. The research findings indicate that indigenous communities have a cultural protection system based on collective values, spirituality, and social control. However, the national legal system still does not fully accommodate the collective and intergenerational nature of indigenous cultural expressions, resulting in communities often losing legal control over their cultural heritage. The discussion reveals that existing regulations tend to use an administrative and individualistic approach, which is less in keeping with the character of customary law. In conclusion, a legal pluralism approach is needed to constructively integrate customary law into the national legal system. Strengthening the capacity of customary institutions and formal recognition of the collective rights of indigenous communities are key to maintaining the sustainability of traditional cultures amid the challenges of globalization.